Identification and functional analysis of novel precursor genes in cyclic peptide biosynthesis in Pseudostellaria heterophylla - Jiao Xu; Wei Zheng; Xiaohong Ou; Hua He; Changgui Yang; Lanping Guo; Chenghong Xiao; Weike Jiang; Guoping Shu; Tao Zhou (BMC Plant Biology)
Abstract Background Pseudostellaria heterophylla, a member of the Caryophyllaceae family, is widely used in traditional Chinese medicine due to its bioactive cyclic peptides (CPs) with immunomodulatory functions. Caryophyllaceae- like CPs, one of the largest types plant-derived CPs, typically consist of 5–12 amino acids and are derived from ribosomally synthesized peptide precursors. The diversity of CPs arises from variations in their core peptide sequences. However, the precursor genes responsible for Caryophyllaceae-like CPs biosynthesis in P. heterophylla remain largely uncharacterized. Results In this study, barcoding PCR combined with high-throughput sequencing was used to efficiently genotype precursor genes encoding CPs in P. heterophylla. This approach enabled the identification of known and novel precursor genes, including prePhHB_1, prePhHB_2, prePhPE and prePhPN. The core peptide regions showed high variability, while the leader and follower regions were relatively conserved, with a few nucleotide mutations. Tissue-specific expression analysis revealed that prePhHB was predominantly expressed in the phloem and fibrous roots, while prePhPE was specifically expressed in the xylem. prePhPN exhibited low expression level and was mainly detected in the phloem and stem. Moreover, the expression of these precursor genes was responsive to abscisic acid and nitrogen stress. RNA in situ hybridization revealed that prePhPE transcripts were primarily localized in the xylem and phellem of the roots. Transient co-expression in Nicotiana benthamiana indicated that prePhPE is involved in the biosynthesis of Pseudostellarin E (PE). Conclusions Barcoding PCR combined with high-throughput sequencing provides an effective strategy for investigating CP precursor genes, including those with low expression. The results reveal conserved features in CP precursor genes and highlight a previously unrecognized mechanism contributing to CP diversity. The prePhPE gene was identified as the precursor gene of PE, which accumulates mainly in the xylem of P. heterophylla roots. prePhPN may be a precursor gene for a novel CP.